Risk management and its implications. - Chua, Cheng Zhi. (2012)
This study aims to investigate the influence and impact derivatives or non-derivatives hedging have on firms’ performance. Various sub-sample analysis are performed to identify and investigate trends and correlations specific to a particular group, such as firms affected by interest rate risk, firms with foreign sales ratio more than 0, to name a few. Sub-sample analysis are conducted so that our study results could be more specifically and accurately related to the firms out there in the real world. A descriptive study is carried out, using 1,500 firms from the S&P 1500 Composite Index. Our paper discusses the economic significance with regards to the results of the variables. Our research findings show that the more a firm engages in derivatives hedging, the lower the firm’s risk. Our findings also pointed out that financial service firms are indeed less likely to use derivatives hedging as compared to non-financial services firms. However, it is observed that firms tends to prefer non-derivatives hedging to hedge for both their interest rate and exchange rate risk.